Comprehensive dental management in a pediatric patient, with a preventive and psychological approach: Case Report - Cruz Gallegos, Alexander (2019)
Carious lesions have been the main cause of premature loss of dental pieces in the deciduous dentition, there are a number of treatments which are focused on the prevention of the dental organ, to restore the anatomy of the dental pieces or the exodontics thereof. The premature loss of individual or multiple way can trigger disorders such as: limitation in basic functions, decrease in the length of the dental arches, and reach the point of decreasing the child's self-esteem. The case of a 6-year-old male patient with mixed, asymptomatic dentition, with the diagnosis of dental caries, pulp pathology and dental position anomaly is presented. The following procedures were performed; Pulpectomies, simple restorations and exodontics, to culminate in the placement of a functional orthopedic device. Upon completion of the treatment, the objective was to preserve the dental structure, bone support, and oral mucosa, with a complete clinical and radiographic diagnosis, accompanied by an appropriate behavior management technique, so that in this way masticatory functions, swallowing and phonation, are restored, and provide a harmonious dental aesthetic, improving the child's self-esteem.